Association between Metabotropic Glutamate Receptor 1 Polymorphism and Cardiovascular Disease in Korean Adults - Shin, Yoonjin; Park, Jaehyun; Won, Sungho; Kim, Yangha (Journal of lipid and atherosclerosis, 2017)
Objective: The mGluR1 (metabotropic glutamate receptor 1) gene, a G protein–coupled receptor, is known to mediate perceptions of umami tastes. Genetic variation in taste receptors may influence dietary intake, and in turn have an impact on nutritional status and risk of chronic disease. We investigated the association of mGluR1 rs2814863 polymorphism with lipid profiles and cardiovascular disease (CVD) risk, together with their modulation by macronutrient intake in Korean adults. Methods: The subjects consisted of 8,380 Koreans aged 40-69 years participating in the Anseong and Ansan Cohort Study, which was a part of the Korean Genome Epidemiology Study (KoGES). Data was collected using self-administered questionnaires, anthropometric measurements, and blood chemical analysis. Results: Carriers of C allele at mGluR1 rs2814863 was associated with decreased high density lipoprotein cholesterol (HDL-C) and increased triglyceride as compared to carriers of TT. Also, carriers of the C allele showed higher fat intake and lower carbohydrate intake than those with carriers of TT. After adjustment for multiple testing using false-discovery rate method, the significant difference of HDL-C, triglyceride, dietary fat, and carbohydrate across genotypes disappeared. Gene-diet interaction effects between rs2814863 and macronutrients intake were not significantly associated with HDL-C and triglyceride levels. However, carriers of C allele demonstrated significantly higher odds of CVD {odds ratio=1.13, 95% CI=1.02-1.25} compared with carriers of TT. Conclusions: Our findings support significant associations between the mGluR1 rs2814863 genotype and CVD-related variables in Korean adults. However, these associations are not modified by macronutrient intake. KCI Citation Count: 0